AKTIVITAS PENANGKAPAN RADIKAL 2,2-DIFENIL-1-PIKRILHIDRAZIL OLEH EKSTRAK ETANOLIK BATANG BROTOWALI (Tinospora crispa (L.) Miers) DAN FRAKSI-FRAKSINYA - Tatang Irianti; Andayana Puspitasari; Ema Suryani (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
We have investigated the antiradical activity of ethanolic extracts of Brotowali stem (Tinospora crispa (L.) Miers) using radical scavenging assay or DPPH radical. Thin layer chromatograms were also studied to estimate the group of compounds that have antiradical activity. The ethanolic extract, ethyl acetate and water fractions were showed coumarin and flavonoid. The DPPH antiradical efficiency values of ethyl acetate fraction was the highest antiradical activity namely 200 µg/ mL of this fraction was able to inhibit 53.57% DPPH radicals.